2016
DOI: 10.1111/jcmm.12911
|View full text |Cite
|
Sign up to set email alerts
|

The Uyghur population and genetic susceptibility to type 2 diabetes: potential role for variants in CAPN10,APM1 and FUT6 genes

Abstract: Genome‐wide association studies have successfully identified over 70 loci associated with the risk of type 2 diabetes mellitus (T2DM) in multiple populations of European ancestry. However, the risk attributable to an individual variant is modest and does not yet provide convincing evidence for clinical utility. Association between these established genetic variants and T2DM in general populations is hitherto understudied in the isolated populations, such as the Uyghurs, resident in Hetian, far southern Xinjian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…H antigens are precursors of ABO and Lewis b histo-blood group antigens that are expressed on mucosal surfaces [ 5 ]. Recent studies have shown suggestive associations between variants of FUT2 with diabetes and body mass index [ 23 26 ].…”
Section: Co-factors or Regulators Of Co-factors Essential For The Tramentioning
confidence: 99%
“…H antigens are precursors of ABO and Lewis b histo-blood group antigens that are expressed on mucosal surfaces [ 5 ]. Recent studies have shown suggestive associations between variants of FUT2 with diabetes and body mass index [ 23 26 ].…”
Section: Co-factors or Regulators Of Co-factors Essential For The Tramentioning
confidence: 99%
“…[ 7 , 19 , 23 ] The inherent genetic differences between ethnic group is to be responsible, just like the opposite trends of the calpain-10 rs3792267 allele and T2DM between the Uyghur and Chinese populations. [ 24 , 25 ] In 2011, Han et al [ 26 ] conducted a meta analysis to explore the association between SNPs of adiponectin gene and T2DM, and the results showed that the adiponectin rs266729 G allele was a risk factor for T2DM, with the pooled OR (95% CI) of 1.07 (1.03, 1.11, P = .001) for G versus C allele. However, the study did not provide the rs266729 genetic effect on the development of T2DM in different populations.…”
Section: Discussionmentioning
confidence: 99%
“…is particularly interesting given its controversial association with T2D risk. It was the first T2D susceptibility gene identified in linkage studies (HORIKAWA et al 2000), with multiple subsequent GWAS or candidate gene studies having also identified an association between variants near CAPN10 and T2D risk and other diabetes-related phenotypes (BAIER et al 2000;EVANS et al 2001;OROZCO et al 2014;IBRAHIM et al 2015;CUI et al 2016;ZHAO et al 2016;BAYRAMCI et al 2017;HOU et al 2017;CASTRO-MARTINEZ et al 2018). However, many other studies failed to replicate these findings (HEGELE et al 2001;TSAI et al 2001;KHAN et al 2014;AL-SINANI et al 2015;PLENGVIDHYA et al 2015;ZHANG et al 2019).…”
Section: Among the Most Significant Genes Whose Expression Is Regulatmentioning
confidence: 99%